Sources of black Sigatoka resistance in wild banana diploids - Fernanda dos Santos Nascimento; Yan Moreira Sousa; Anelita de Jesus Rocha; Claudia Fortes Ferreira; Fernando Haddad; Edson Perito Amorim (Revista Brasileira de Fruticultura, 2020)
Abstract Black Sigatoka (black leaf streak disease) is caused by the fungus Mycosphaerella fijiensisMorelet. This phytopathogen colonizes banana leaves, resulting in reduced photosynthesis and decreased productivity. Fungicide applications are useful to control black Sigatoka; however, they increase production costs and can have adverse environmental and health impacts. The cultivation of resistant cultivars is regarded as a more economically viable option. The objective of this study was to perform diploid phenotyping in a set of wild banana accessions to identify resistant genotypes. A total of 31 accessions (30 with AA genome and one with AB genome) were phenotyped based on the presence of disease symptoms using a scoring scale. The area under the disease progress curve (AUDPC), the disease severity index (DI), and the disease severity increase index (DII) were estimated. The DII variable proved to be efficient in identifying banana accessions with black Sigatoka resistance. Likewise, the selection index for ranking accessions with moderate black Sigatoka resistance allowed us to identify those genotypes with the highest quantitative resistance. Five diploid accessions (Krasan Saichon, Zebrina, Birmanie, Nº 118, and Tuu Gia) were found to be resistant to this fungal disease; eight accessions (PA Rayong, Pisang Cici, Malaccensis 1, 028003- 01, Microcarpa, Pisang Lidi, Lilin, and Malbut) were moderately resistant.